Pharmacological importance of TG12 from tachykinin and its toxicological behavior against multidrug-resistant bacteria Klebsiella pneumonia - Raju, Stefi V.; Sarkar, Purabi; Pasupuleti, Mukesh; Saraswathi, Nambiappan T.; Arasu, Mariadhas Valan; Al-Dhabi, Naif Abdullah; Esmail, Galal Ali; Arshad, Aziz; Arockiaraj, Jesu (Elsevier, 2021)
Development of antimicrobial drugs against multidrug-resistant (MDR) bacteria is a great focus in recent years. TG12, a short peptide molecule used in this study was screened from tachykinin (Tac) protein of an established teleost Channa striatus (Cs) transcriptome. Tachykinin cDNA has 345 coding sequence, that denotes a protein contained 115 amino acids; in which a short peptide (TG12) was identified at 83–94. Tachykinin mRNA upregulated in C. striatus treated with Aeromonas hydrophila and Escherichia coli lipopolysaccharide (LPS). The mRNA up-regulation was studied using real-time PCR. The up-regulation tachykinin mRNA pattern confirmed the immune involvement of tachykinin in C. striatus during infection. Further, the identified peptide, TG12 was synthesized and its toxicity was demonstrated in hemolytic and cytotoxic assays using human erythrocytes and human dermal fibroblast cells, respectively. The toxicity study exhibited that the toxicity of TG12 was similar to negative control, phosphate buffer saline (PBS). Moreover, the antibiogram of TG12 was active against Klebsiella pneumonia ATCC 27736, a major MDR bacterial pathogen. Further, the antimicrobial activity of TG12 against pathogenic bacteria was screened using minimum inhibitory concentration (MIC) and anti-biofilm assays, altogether TG12 showed potential activity against K. pneumonia. Fluorescence assisted cell sorter flow cytometer analysis (FACS) and field emission scanning electron microscopy (FESEM) was carried on TG12 with K. pneumonia; the results showed that TG12 significantly reduced K. pneumonia viability as well as TG12 disrupt its membrane. In conclusion, TG12 of CsTac is potentially involved in the antibacterial immune mechanisms, which has a prospectus efficiency in pharma industry against MDR strains, especially K. pneumonia.